From the central pivot to the peripheal knee injuries in the skier: a narrative review: Knee injuries in the skier: a narrative review - Jannelli, Eugenio; Ferranti Calderoni, Enrico; Ivone, Alessandro; Rivellino, Maria Concetta; Ghiara, Matteo; Castelli, Alberto; Zanon, Giacomo; Benazzo, Francesco (Acta Biomedica Atenei Parmensis, 2019)
The improvement in the technology in the last 20 years has showed its main effect on the increase of the speed in the curves, thus leading to a rise of knee injuries. In fact, the most injured zone of the body was the knee (35,6 %) and the distal part of the lower body (11,5%), with ACL lesion as the most frequent diagnosis (49% of all the injuries to the knee) due to a trauma in valgus and external rotation in most of cases. The MCL is involved in the 15-20% of the cases while the LCL in only the 4,2% of the patients. Unique epidemiology and distinct mechanisms of injuries are peculiar for skier’s knee while evaluation and treatment is similar to evaluation and treatment of knee injuries in other athletes. In this narrative review we aimed to highlight the current evidences in skiers’ traumatology with special focus on the treatment nowadays proposed in the international literature and to the return to sport.